Association between the sarcopenia index and abnormal liver function in the adult population in the United States: a cross-sectional study - Xu, Jian; Xu, Zhi-Xiang; Yang, Qi-Fan; Zhuang, Jing; Zhu, Xin; Yao, Jun (Frontiers in Medicine, 2023)
Background The objective of this study was to explore the association between the sarcopenia index and abnormal liver function in adult individuals in the United States. Methodology This study employed a rigorous cross-sectional analysis of data derived from the National Health and Nutrition Examination Survey (NHANES) conducted between 2017 and 2018. The primary objective was to investigate the correlation between the sarcopenia index and abnormal liver function. To achieve this, an advanced multivariate regression model was utilized, allowing for comprehensive analysis and meticulous adjustment of relevant variables. To ensure the robustness of the findings, a visually appealing smooth curve was constructed, and a two-stage regression model was applied for validation. Additionally, a detailed gender-stratified analysis was conducted to further explore the association between the sarcopenia index and abnormal liver function within distinct subgroups. Results Through our rigorous participant selection process, a total of 1756 individuals were included in the study. The meticulously adjusted multivariate regression model revealed a significant negative association between the sarcopenia index and abnormal liver function, with an adjusted odds ratio (OR) of 0.73 and a 95% confidence interval (CI) ranging from 0.63 to 0.86. The robustness of this association was further supported by the visually appealing smooth curve plot. Moreover, in the gender-stratified subgroup analysis, after meticulous adjustment for confounding factors, notable differences in this association emerged (males: OR = 0.8, 95% CI: 0.66–0.98; females: OR = 0.61, 95% CI: 0.47–0.79). Conclusion This cross-sectional study yields robust evidence indicating a negative correlation between the sarcopenia index and abnormal liver function, predominantly observed among females.